If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 2) + 4 = 0 Reorder the terms: 3(2 + n) + 4 = 0 (2 * 3 + n * 3) + 4 = 0 (6 + 3n) + 4 = 0 Reorder the terms: 6 + 4 + 3n = 0 Combine like terms: 6 + 4 = 10 10 + 3n = 0 Solving 10 + 3n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3n = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3n = 0 + -10 3n = 0 + -10 Combine like terms: 0 + -10 = -10 3n = -10 Divide each side by '3'. n = -3.333333333 Simplifying n = -3.333333333
| 3m-8+m=12-2m+10 | | 15=5a+2b+c | | 4x+40=0 | | 0.1-2y=-5.9 | | F(x)=2x^2+3(4x)+17 | | 4x^2-20x-4=0 | | (2r-13)-(6r+4)= | | 3.6r-8.8=5.6 | | 2x^2+25x-168=0 | | z-6.2=7.94 | | 100[0.07(y+6)]= | | 6.8(2y+4)-1.7(3y-6)= | | 14x^2=11 | | 11x^2+11x+11=0 | | 4(2x-7)-2x=4(x+6) | | -2y-3y+8= | | 0.08(y-8)+0.20y=0.18y-0.4 | | lnx=0.65 | | 5x+25-70=0 | | 10x^2-18x+8=0 | | 49(p-1)=p(p+35) | | 8d-36=-10d | | 2.5m=55 | | 2x+3+.4x+2=11 | | 7x+x-5=7x+4 | | 2x+3+4x+2=111 | | t(9+t)=2(2t+7) | | 5x+5=-6+3x+25 | | Y=cos^2(3x) | | 3sqrt(x+2)=8 | | [x+4][x+4]=1 | | [x+4]2=1 |